Pengaruh Literasi Keuangan, Financial Technology, dan Motivasi Utilitarian Terhadap Pengelolaan Keuangan Mahasiswa - Eka Fitri Nurjannah; Hero Priono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the effects of financial literacy, financial technology, and utilitarian motivation on student financial management using explanatory quantitative methods. Research subjects were Accounting students at UPN "Veteran" East Java batches 2021-2022, with 88 respondents from 713 students through Slovin formula and simple random sampling. Data collected via Google Form questionnaires using Likert scale, analyzed with PLS-SEM SmartPLS 4.0. Results show financial literacy and financial technology significantly positively affect student financial management, while utilitarian motivation is insignificant. According to Theory of Planned Behavior, rational utilitarian considerations are insufficient to drive students' actual actions due to behavioral control perception and subjective norm influences.